2022
DOI: 10.2174/1871520621666210707095833
|View full text |Cite
|
Sign up to set email alerts
|

Retracted: miR-27b-3p Inhibits Invasion, Migration and Epithelial-mesenchymal Transition in Gastric Cancer by Targeting RUNX1 and Activation of the Hippo Signaling Pathway

Abstract: Background: Gastric cancer (GC) accounts for high mortality, which seriously threatens people’s health. This study set out to probe into the effect and mechanism of miR-27b-3p on invasion and migration of GC. Methods: The miRNA sequence data of GC was acquired from The Cancer Genome Atlas (TCGA) database. The differential expression of miRNAs (DEMis) was acquired through R packages “edgeR” and “limma.” TargetScan, picTar, RNA22, PITA, and miRanda were performed to predict the target gene of miR-27b-3p. Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…studies have revealed that RUNX1 mRNA is associated with metastasis of breast and prostate cancers, with expression inversely associated with tumour aggressiveness. 15,[23][24][25][26] Moreover, RUNX1 has been reported to be involved in several hormone-related solid cancers. 26 Beyond breast cancer, overexpression of RUNX1 was suggested to play a promotive role in endometrioid carcinoma myometrial infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…studies have revealed that RUNX1 mRNA is associated with metastasis of breast and prostate cancers, with expression inversely associated with tumour aggressiveness. 15,[23][24][25][26] Moreover, RUNX1 has been reported to be involved in several hormone-related solid cancers. 26 Beyond breast cancer, overexpression of RUNX1 was suggested to play a promotive role in endometrioid carcinoma myometrial infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…It is also becoming evident that varying levels of RUNX1 expression can be identified as markers of tumour progression not only in haematopoietic system diseases but also in solid tumour diseases 16,22 . Earlier studies have revealed that RUNX1 mRNA is associated with metastasis of breast and prostate cancers, with expression inversely associated with tumour aggressiveness 15,23–26 . Moreover, RUNX1 has been reported to be involved in several hormone‐related solid cancers 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this finding, Zhu et al verified that miR-27b-3p is abnormally upregulated in HCC [ 51 ]. Besides, the role of miR-27b-3p is highly comparable not only in HCC but also in other tumors [ 27 , 28 , 52 ]. Furthermore, Wu et al found that miR-27b-3p downregulation causes chemoresistance in colorectal cancer (CRC), revealing the anti-cancer effect of miR-27b-3p in CRC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial whether abnormally expressed miR-27b-3p acts as an oncogene or an anti-oncogene in cancer. miR-27b-3p inhibited malignant progression capacity by targeting RUNX1, Nrf2, and MARCH7 in gastric cancer, esophageal squamous cell carcinoma, and endometrial cancer, respectively [ 25 27 ]. In contrast, miR-27b-3p accelerated tumor progression via PPARG and HOXA10 in triple-negative breast cancer and colorectal cancer, respectively [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%